WTO negotiations and agricultural trade liberalization: the effect of developed countries' policies on developing countries - Diaz-Bonilla, E.; Diaz-Bonilla, E.; Frandsen, S. E.; Frandsen, S. E.; Robinson, S.; Robinson, S. (Wallingford :CABI, 2006)
This book arises from a joint research project between the Food and Resource Economics Institute in Denmark and the Food Policy Research Institute in Washington. It analyses the effects of developed countries' agricultural policies on developing countries. The main focus is on food security, poverty and other topics such as multifunctionality, biotechnology and regional agreements, as an input to policy reform within the World Trade Organization trade negotiations. The results have been presented in a way that is usable by interested parties in developing countries. The book will be of interest to those researching and working in agricultural economics, development studies and law. It has 14 chapters and a subject index.
Keywords: EE110 - Agricultural Economics; EE116 - Food Economics, (New March 2000); EE120 - Policy and Planning; EE600 - International Trade; EE950 - Income and Poverty; WW000 - Biotechnology (General), (Revised June 2002); Developed Countries; Developing Countries